Cost-effectiveness and cost-utility analysis of the use of clopidogrel and pantoprazole in comparison with clopidogrel and omeprazole for the secondary prevention of myocardial infarction in Iran - Mohammadreza Amirsadri; Valiollah Hajhashemi; Amir Shahriar Asemi (Wolters Kluwer Medknow Publications, 2021)
Objective: Gastrointestinal bleeding, a side effect of clopidogrel, is usually prevented by proton-pump inhibitors (PPIs). Due to omeprazole's inhibitory effects on the liver enzyme CYP2C19, its concomitant use with clopidogrel is argued to increase the risk of myocardial infarction (MI) recurrence, as CYP2C19 activates clopidogrel. Pantoprazole as an alternative PPI has shown no inhibitory effect on CYP2C19. This study investigates the cost-effectiveness of concomitant use of clopidogrel and pantoprazole in MI patients compared to the simultaneous use of clopidogrel and omeprazole. Methods: We used the Markov-modeling technique with a hypothetical cohort of 1000 acute MI patients aged 55 years using Microsoft Excel 2013 software. The study was done from the payer perspective, and a lifetime horizon with 1-year cycles was considered in the model. Life-years gained (LYG) and quality-adjusted life-years (QALYs) were used to quantify the health effects of these interventions. Two separate scenarios of public tariffs and private tariffs with various discount rates (0%, 3%, and 7.2% discounts (only for costs)) were evaluated, and an incremental cost-effectiveness ratio (ICER) was used to report the results. One-way and probabilistic sensitivity analyses were used to deal with uncertainty. Data were sourced from published literature and tariff book of the Iranian ministry of health. Findings: The estimated ICERs were 342 USD/QALY and 236 USD/LYG per patient for the base-case scenario. Conclusion: Abiding by the WHO threshold for cost-effectiveness, the concomitant use of pantoprazole and clopidogrel can be considered cost-effective compared to the use of omeprazole and clopidogrel.